Defining the relationship between arm and leg blood pressure readings: a systematic review and meta-analysis. Issue 4 (April 2019) - Sheppard, James P.; Albasri, Ali; Franssen, Marloes; Fletcher, Ben; Pealing, Louise; Roberts, Nia; Obeid, Amira; Pucci, Mark; McManus, Richard J.; Martin, Una
Abstract : Objectives: To define the relationship between arm and leg blood pressure (BP) to inform the interpretation of leg BP readings in routine clinical practice where arm readings are not available. Methods: Systematic review of all existing studies comparing arm and leg BP measurements. A search strategy was designed in MEDLINE and adapted to be run across six further databases. Articles were deemed eligible for inclusion if they measured and reported arm and leg BP taken in the supine position and/or the difference between the two. Mean values for arm–leg BP difference and measures of precision [95% confidence intervals (CIs) or SD] were extracted and entered into a random-effects meta-analysis. Results: A total of 887 articles were screened and 44 were included in the descriptive analyses, including 9771 patients. In the general population, ankle SBP was 17.0 mmHg (95% CI 15.4–21.3 mmHg) higher than arm BP in the supine position. For DBP, there was no difference between arm and ankle BP (−0.3 mmHg, 95% CI −1.5–1.0 mmHg). In patients with vascular disease, SBP was −33.3 mmHg (95% CI −59.1 to −7.6 mmHg) lower in the ankle compared with the arm. Conclusion: This is the first review to provide empirical data defining the difference between BP in the arm and leg in the general population. Findings suggest a diagnostic threshold of 155/90 mmHg could be used for diagnosing hypertension when only ankle measurements are available in routine practice. Abstract : Supplemental Digital Content is available in the text